Research on path planning of robotic ultrasonic surface strengthening for turbine blade based on dynamic response of ultrasonic surface strengthening - Shanxiang Fang; Qinjian Zhang; Weidong Cheng; Jiwu Wang; Chang Liu; Kang Han (Advances in Mechanical Engineering, 2019)
In order to realize the automatic strengthening for turbine blades, a path planning method for robotic ultrasonic surface strengthening is proposed. A constitutive model of nonlinear isotropic strengthening–kinematic hardening is analyzed to establish the dynamic response model of ultrasonic surface strengthening on the turbine blade. According to the dynamic response model, the impact depth of the ultrasonic working head was obtained. Then, a path planning method of robotic ultrasonic surface strengthening for turbine blades is proposed on the basis of impact depth of working head, and it can improve both the uniformity of path distribution and contour accuracy. It not only ensures the processing accuracy but also meets the uniformity requirement of coverage. This path planning method provides a new surface strengthening technology for turbine blades.